THE ROLE OF ISLAMIC FINANCIAL LITERACY IN PREVENTING ONLINE SLOT GAMBLING AMONG GEN Z - Anggara; Yunia Fauzia, Ika (Universitas Muhammadiyah Surabaya, 2024)
In the digital era, Generation Z (Gen Z) encounters numerous challenges and opportunities driven by the rapid advancement of information technology, including the increasing prevalence of online gambling. This study investigates the critical role of Islamic financial literacy in mitigating online gambling, with a particular focus on online slot gambling, a rapidly growing segment. Utilizing a qualitative approach with a phenomenological method, the research was conducted in Surabaya and involved participants from within and outside the city to provide a comprehensive perspective. The findings highlight that several factors influence the escalation of online gambling among Gen Z. Internally, the challenge lies in the inadequate internalization of relevant norms and values, which leads to poor financial decision-making. Externally, factors such as economic pressures and technological advancements make online gambling more accessible and appealing, thus exacerbating the issue of rising addiction and financial instability among vulnerable individuals. This study emphasizes the urgent need to enhance Islamic financial literacy among Gen Z. By integrating Islamic financial principles into educational initiatives and personal finance management, individuals can be better equipped to make informed decisions, avoid gambling temptations, and manage their finances responsibly. Strengthening Islamic financial literacy is crucial for reducing the negative impacts of online gambling and fostering a more financially prudent generation.